Lipoblastomatosis: An unusual midline neck mass in a young child. (January 2021) - Jain, Rhea; Betancourt, Renée L.; Rose, Austin S.
Abstract: Lipoblastomatosis is an extremely rare condition and is often not recognized prior to final pathologic analysis. In this case, a two-year-old female child presented with a non-tender, submental midline neck mass which had enlarged very slowly over the course of five months. The differential diagnosis included lipoma, lymphatic malformation, and thyroglossal duct cycst and a surgical excision was planned. The child was consented for a possible Sistrunk procedure if necessary. Intraoperatively, the mass was adherent to the hyoid bone and clear mucoid drainage was noted during resection leading the team to further weight the possibility of thyroglossal duct cyst and proceed with a Sistrunk procedure. Ultimately, final pathology revealed the diagnosis of lipoblastomatosis.